ON A – OPTIMILITY DESIGN FOR SOLVING SECOND - ORDER RESPONSE SURFACE DESIGN PROBLEMS - Akra, Ukeme P.; Isacc, Anthony A.; Michael, Itoro Tim; Akpan, Usenobong B.; Akpan, Stephen S. (FUDMA JOURNAL OF SCIENCES, 2025)
Optimality criteria is a mechanism used for measuring the betterment of a design. Several traditional optimality criteria such as A, D, E, T, IV, etc, are the classes of optimal criterion for the test of optimum design. A – Optimality criterion as one of the traditional alphabetical criterion is used to examine the right selection of a design using second – order response surface models. In this paper, an algorithm and flowchart in line with a program to solve A – optimal design problem using second – order response surface model are developed. This paper also aimed to juxtaposing the accuracy between the manual and the programming technique in solving A – optimal problem. A six points of two designs with two explanatory variables were formulated to test the two methods. The result shows that the programming technique outperformed better than the manual method and it also minimizes error.